2021
DOI: 10.3389/fpubh.2021.712255
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Knowledge and Practices Regarding Asthma in Jordan: A Cross-Sectional Study

Abstract: Objectives: Asthma is a chronic non-communicable disease that causes significant morbidity and mortality and requires ongoing clinical care. Appropriate knowledge by physicians is vital in the management of asthma. Therefore, this study aims to explore and identify the gaps in physicians' knowledge and practices concerning the management of asthma.Methods: A cross-sectional study using an online survey was conducted in Jordan to understand the gap in knowledge and practices in the management of asthma among ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The results showed that the ICS/LABA combination reduced asthma exacerbations compared to ICS alone [ 6 ]. Furthermore, asthma is one of the main non-communicable diseases, with a global prevalence exceeding 339 million people and is most commonly prevalent among children [ 7 , 8 , 9 ]. According to the WHO, annual asthma-associated worldwide deaths exceeded 400,000 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the ICS/LABA combination reduced asthma exacerbations compared to ICS alone [ 6 ]. Furthermore, asthma is one of the main non-communicable diseases, with a global prevalence exceeding 339 million people and is most commonly prevalent among children [ 7 , 8 , 9 ]. According to the WHO, annual asthma-associated worldwide deaths exceeded 400,000 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 23 Previous studies reported a good knowledge of physicians about the characteristics of asthma, this was also in line with the results reported in our study as it showed that around 70% of the study sample had a good knowledge about asthma characteristics. 21 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…These results are lower than those reported in previous studies in Jordan and southwest Nigeria. 21 , 23 Investigating the risk factors of asthma can be challenging, and in many cases patients are likely to be referred to specialised doctors and this could be the reason for the low percentage about the knowledge of asthma triggers, especially knowing that only 30% of the study sample were pulmonologists, while the majority of the study participants were from different specialities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations